Arabiyatuna Board Game - Abdul Rahim, Abdul Hadi; Hussin, Muhammad Hafizuddin; Roslan, Muhammad Hanis; Awang Ali, Mohammad Amnan (Pusat Asasi, UiTM Kampus Dengkil, Selangor, 2022)
This research focuses on a novel approach to learning Arabic through the Arabiyatuna board game. The board game includes 50 comprehension and grammar problems in Arabic. According to earlier studies, pupils' comprehension of language learning improves when they play games. The research's goals are to assess students' understanding of the Arabic language at the basic level and to link such knowledge to an interactive learning method. This board game is currently undergoing testing and will be released as an app in the future. This initiative will have a big impact on future Arabic language acquisition. This study will improve students’ grasp of Arabic and their attitudes about the language.